P12 Acceptability of a parental early warning tool: outcomes from a feasibility study of parental home monitoring and assessment. (2nd March 2016) - Gaskin, K; Cooper, L; Mohammed, N; Rooney, M; Barron, D
Abstract : Aim: The principle aim was to explore the feasibility of a Congenital Heart Assessment Tool (CHAT) as part of a home monitoring programme (HMP) for parents going home with their infant between the first and second stage of surgery for complex congenital heart disease, including single ventricle and systemic shunt dependent conditions. This paper also reports on how many times parents made urgent contact with health care professionals (HCP) and the acceptability of the CHAT and HMP from the parents' perspective. Background: HMPs were developed to encourage early recognition of deterioration in infants who are at risk of potentially life threatening events between the first and second surgical stage and focus on parents obtaining daily measurements of their infant's oxygen saturations (SpO2 ) and weight (wt.). In this study, the HMP was compared with the CHAT, which was designed for ease of use and incorporated a traffic light system enabling parents to assess the severity of their infant's condition through individualised parameters. Green assessment directs parents to 'carry on as normal'; amber triggers a phone call to the ward to discuss management; a red response, indicates the infant is seriously ill and parents are advised to phone for an ambulance immediately Method: A mixed methods approach was adopted; data was collected at four time points (at discharge [T0]; 2 weeks after discharge [T1], 8 weeks after [T2] and after stage two surgery [T3]) using self-report tools, semi-structured interviews and daily diaries. Parents were recruited between August 2013 and February 2015. After obtaining consent parents were randomised into either: Gp A, measured SpO2 and wt. daily and assessed their infant daily using the CHAT; Gp B, used the CHAT alone or Gp C, received standard discharge care. Results: Parents of 80 infants were identified as eligible; 13 mothers and 4 fathers of 13 infants consented to participate (Gp A=5; Gp B=4; Gp C=4). Following recruitment one mother (Gp A) did not participate. The time period T0 to T3 ranged from 62–228 days; all infants survived the first two stages of surgery. The qualitative data set included 38 interviews. Four main themes emerged regarding the CHAT: it prepared parents for the signs to look for at home; it was easy to use; it increased parental confidence and gave them reassurance to call for advice when they noticed that something was different. Themes emerging regarding the HMP: parents felt daily wt. were not necessary; the scales were ' a hindrance more than helpful', especially when they were getting behind with other aspects of their infant's care. The SpO2 was more reassuring; could be used at any time and gave peace of mind. Gp C parents talked about the normalisation of going home and a recognition that the HMP may have made them more reliant and anxious. Diary entries indicated: only two diaries were fully used; total CHAT amber triggers (n = 7 occasions, no admissions); red triggers and drop in SpO2 (n = 1, 1 local hospital readmission); calls to ward staff (n = 13, including Gp C); other contact with HCP (n = 7) no contacts were cardiac in origin. Conclusions: The CHAT was acceptable and gave parents confidence to know when there was a change in their infant's condition. There were no early admissions for stage two based on a trigger of the CHAT or HMP. Small recruitment numbers limited comparison of groups.